E-025 The use of intra-arterial rt-PA improves functional outcomes over mechanical thrombectomy alone in patients undergoing acute stroke therapy. (4th July 2012) - Rai, A; Carpenter, J; Roberts, T
Abstract : Background: The paradigm of endovascular stroke therapy, especially with the newer devices aimed at rapid revascularization, is shifting from local intra-arterial thrombolysis (IAT) to mechanical thrombectomy (MT). There is lack of clear data comparing the two modalities. While revascularization is the obvious desirable endpoint of any procedure, the benefit of the therapy can only be judged by improved functional outcome. The objective of this study was to compare IAT and MT for large vessel strokes. Methods: 123 patients who had undergone endovascular therapy with IAT alone, MT alone or both (IAT+MT) were selected. The inclusion criteria were age ≥18, internal carotid artery terminus (ICA-T), middle cerebral artery (M1) or isolated proximal M2 branch (M2) occlusions. A TIMI-2 or three categorized successful recanalization. The primary endpoint was a 90-day favorable outcome (mRS≤2). Results: The mean age and baseline NIHSS was 68.2±17.3 years and 16.2±7.3. There were 64 (52%) female patients. Occlusion site distribution: ICA-T 29 (23.6%), M1 69 (56.1%) and M2 25 (20.3%). There were 43 patients (35%) who received IAT, 30 patients (24.4%) who underwent MT and 50 patients (40.6%) who had IAT+MT. The type of treatment administered was significantly associated with the occlusion site (p<0.0001); ICA-T (IAT: 10.3%, MT: 37.9%, IAT+MT: 51.7%), M1 (IAT: 31.9%, MT: 27.5%, IAT+MT: 40.6%) and M2 (IAT: 72%, MT:0%, IAT+MT: 28%). A favorable outcome was seen in 55 patients (44.7%), mortality in 40 patients (32.5%) and successful recanalization in 70 patients (56.9%). The highest recanalization of 70% was seen for MT only group while the IAT and IAT+MT groups had recanalization rates of 34.9 and 34% respectively (p=0.002). A favorable outcome was seen in 62.8% of the IAT, 26.7% of the MT and 40% of the IAT+MT group (p=0.006). In patients who did not receive any IAT, the rate of favorable outcomes was 26.7% as opposed to a favorable outcome rate of 50.5% in patients who received IAT whether alone or in combination with MT (OR 0.36, 95% CI 0.14 to 0.88, p=0.01). However when analyzed by occlusion site, there was no difference between the outcomes based on IAT use for ICA-T occlusions (p=0.4) but significantly higher favorable outcomes were associated with IAT use for M1 occlusions, 48% with IAT use vs 21% when no IAT was utilized (OR 0.29, 95% CI 0.08 to 0.99, p=0.03). There was no difference in the rate of post-procedure hemorrhage with IAT use (23.5%) vs no IAT use (24.5%) (p=0.9). Likewise the mortality rate was not significantly different based on the treatment type. Conclusion: Despite having a lower recanalization rate, IAT is associated with significantly better function outcomes as compared to an intervention without IAT use. MT may achieve a higher immediate revascularization but it does not necessarily translate into equally improved outcomes. A likely explanation is the local and regional thrombolytic state induced by rt-PA at the site of occlusion and within the vascular bed distal to the occlusion. MT on the other hand may recanalize the "target" vessel but does not affect distal smaller emboli and may in fact be their cause secondary to clot fragmentation. Competing interests: A Rai: Stryker Neurovascular. J Carpenter: Codman Neurovascular, Genentech, EV3. T Roberts: None.